Trends of Influenza’s Symptoms Drug Search Terms in Indonesian-Language using Google Trends in the Covid-19 Pandemic - Nailis Syifa'; Nurul Purborini (Borneo Journal of Pharmacy, 2022)
Covid-19 has spread globally and causes severe acute respiratory syndrome. The symptoms of covid-19 have similarities with influenza, such as cough, fever, runny nose, and sore throat. Therefore, the internet sources tend to have an increasing search related to influenza symptoms drugs. This study aims to assess the search trend of influenza symptoms drugs using google trend analysis in Indonesia. We explore google trend analysis using search terms in the Indonesian language related to influenza symptoms drugs from December 6th, 2020 to November 30th, 2021. The positive confirmed cases were obtained from the Indonesian government website https://covid19.go.id/. Our results demonstrated the increasing search terms related to influenza drug symptoms during July and August. The highest term search was “obat batuk”. The positive covid-19 confirmed cases in Indonesia increased during July and August. During the peak of the covid-19 outbreak in Indonesia in July-August 2021, there was an increase in google trends searching related to influenza’s drug symptoms.